Rare case of jugular bulb diverticulum causing massive bleeding during tympanoplasty and delayed facial nerve paralysis - Shmuel Wechsler; Rona Burla; Haim Gavriel; Shani Avnery Kalmanovich; Ronen Levite; Yael Garti Gross (Acta Oto-Laryngologica Case Reports)
Jugular bulb (JB) diverticulum is a rare skull-base venous anomaly. It has seldom been reported to extend into the middle ear cavity with bony dehiscence and can rarely cause facial nerve canal dehiscence. We report a case of a young patient with dehiscent JB diverticulum that caused massive bleeding during tympanoplasty surgery, controlled with fibrillar combined with bone wax. On postoperative day 3, the patient developed delayed complete facial nerve paralysis (DCFNP) and was eventually treated with embolization of the jugular diverticulum and the sigmoid sinus and continued to revision surgery for facial nerve decompression, resulting in facial nerve recovery. This case emphasizes the importance of surgical intervention in DCFNP when short-term pressure, such as temporary hematoma or edema, has been ruled out and the strategies available for embolization of JB anatomical malformations. We also discuss the importance of routine preoperative comuted tomography (CT) in middle ear surgeries and review the possible methods for bleeding control during ear surgery.